Biodiversity of the birds in the Van Long wetland nature reserve in the Ninh Binh province - Hung, Nguyen Lan (Academia Journal of Biology, 2015)
The surveys on the avifauna of the Vanlong wetland nature reserve in the Ninhbinh province were carried out for 2 years: 2001 and 2002. There are 72 species belonging to 33 families of 14 orders recorded in the Vanlong reserve. Among them, 3 species are listed in the Red Data Book of Vietnam (2000): silver pheasant (Lophura nycthemera), brown fish Owl (Ketupa zeylonensis) and tickell’s hornbill (Ptilolaemus tickelli). The diversity of each order isn’t high, having average 2 families for one order. The highest quantity of them is from December to February, up to 2000 observed individuals. The Vanlong reserve has potentials to develop the eco-tourism, particularly in bird watching.